Structural equations modeling: Fit Indices, sample size, and advanced topics - Iacobucci, Dawn (Journal of Consumer Psychology, 2010)
AbstractThis article is the second of two parts intended to serve as a primer for structural equations models for the behavioral researcher. The first article introduced the basics: the measurement model, the structural model, and the combined, full structural equations model. In this second article, advanced issues are addressed, including fit indices and sample size, moderators, longitudinal data, mediation, and so forth.